Identification of two antagonistic fungi and antifungal activity analysis against anthracnose in tea plant (Camellia sinensis) - Lu Liu; Haonan Guan; Mengmin Jiao; Zhonglian Ma; Yumeng Bao; Xingcui Xie; Yafeng Ma; Jie Zhou; Lu Bao; Youben Yu; Wenzhao Wang (Beverage Plant Research)
Anthracnose, a prevalent disease affecting tea leaves, poses a significant threat to tea yield and quality. Current control measures predominantly rely on chemical pesticides, raising concerns over environmental contamination and pesticide residues. In exploring biological alternatives, 13 epiphytic fungi were isolated from healthy tea leaves, with nine demonstrating non-pathogenic characteristics. Through a plate confrontation test, strains exhibiting high antagonistic activity against anthracnose were identified, notably En10 and En12, which effectively suppressed the growth of tea plant anthracnose pathogens. Morphological and molecular analyses classified En10 as Aspergillus niger and En12 as Talaromyces. The application of spore suspensions of varying concentrations of En10 and En12 onto tea leaves revealed a significant reduction in anthracnose incidence. Notably, En12 exhibited the capacity to enhance the antioxidant potential of tea leaves. These findings underscore the potential of utilizing antagonistic fungi En10 and En12 for anthracnose control in tea plant, offering valuable insights and technical foundations for biological management strategies against this disease.